A two-step bonding process for preparing 6061/AZ31 bimetal assisted with liquid molten zinc interlayer: the process and microstructure. Issue 19 (2nd October 2022) - Li, Shuai; Zheng, Zhentai; Chang, Liang; Guo, Donghui; Yu, Jinling; Cui, Mengfei
Abstract: In this study, 6061/AZ31 bimetal is manufactured utilizing the two-step bonding progress assisted with liquid molten zinc interlayer. The interfacial microstructure, phase compositions and bonding properties of 6061/AZ31 bimetal are studied. The results show that 6061/AZ31 bimetal is successfully prepared by this process. Different reaction zones are detected on the AZ31 substrate side and 6061 substrate side, which are named as aluminum-zinc reaction zone (Al-Zn RZ) and magnesium-zinc reaction zone (Mg-Zn RZ), respectively. α-Al and β-Zn are detected in the Al-Zn RZ. Mg-Zn RZ contains α-Mg, β-Zn, Al5 Mg11 Zn4, Al6 Mg11 Zn11 and MgZn2, indicating particularly hard and brittle aluminum-magnesium intermetallic compounds (Al-Mg IMCs) are not produced. The whole process of preparing 6061/AZ31 bimetal can be divided into three stages. 6061 aluminum alloy and AZ31 magnesium alloy successively form metallurgical bonds with molten zinc. 6061/AZ31 bimetal is obtained when the liquid molten zinc solidifies again. The formation of 6061/AZ31 bimetal depends on the atomic diffusion and metallurgical reaction. Higher microhardness values are obtained in Al-Zn RZ and Mg-Zn RZ compared with 6061 substrate and AZ31 substrate. The maximum interface microhardness (333 HV) of 6061/AZ31 bimetal is obtained in the MgZn2 layer of Mg-Zn RZ. The maximum shear strength of 6061/AZ31 bimetal is 38.7 MPa, and fracture occurs in the MgZn2 layer. The fracture morphology exhibits the characteristics of brittle fracture.